2002
DOI: 10.1016/s0736-0266(02)00054-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased reflex activation of the peroneus longus following application of an ankle brace declines over time

Abstract: Two experiments were performed to document the time-dependent characteristics of the peroneus longus short latency stretch reflex amplitude following application of an ankle brace. In Experiment I , stretch reflexes were induced in 15 weightbearing subjects during an unbraced condition and braced condition. In Experiment 2, stretch reflexes were induced in 15 weightbearing subjects before and after 3 h of wearing the brace. In Experiment 1, the amplitude of the stretch reflex increased in the braced condition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
4
0
3
Order By: Relevance
“…Nevertheless, a prior study indicated the limited diagnostic value of radiographs for CSI because of the variance of TFO, MCS, and TFCS with ankle rotation. 2,23 Similarly, the results of this research demonstrated that traditional radiography cannot diagnose CSI accurately. Consequently, further imaging methods such as CT or MRI are required.…”
Section: Discussionsupporting
confidence: 54%
“…Nevertheless, a prior study indicated the limited diagnostic value of radiographs for CSI because of the variance of TFO, MCS, and TFCS with ankle rotation. 2,23 Similarly, the results of this research demonstrated that traditional radiography cannot diagnose CSI accurately. Consequently, further imaging methods such as CT or MRI are required.…”
Section: Discussionsupporting
confidence: 54%
“…In people with SCI, for example, changes in Hreflex size and latency evolve from early injury (i.e., the period of spinal shock) to the onset of chronic hyperreflexia [121,122]. People with spastic hyperreflexia due to SCI exhibit less H-reflex decrease from sitting to standing [93], and the Hreflex is inappropriately elevated during the swing phase of Peroneus longus [62][63][64][65][66], tibialis anterior [50,67] Median Abductor pollicis brevis [68][69][70][71], flexor carpi radialis [50,[71][72][73][74][75][76][77][78][79], flexor digitorum superficialis [50,68,80] locomotion [31,36,37,41]. The latter pattern, also observed in stroke, contributes to locomotor impairments such as clonus and foot drop [123].…”
Section: The H-reflexmentioning
confidence: 99%
“…Andere Autoren finden keinen Einfluss [28,29] oder leicht reduzierte Reflexaktivitäten durch Tape [29,30]. Es wird auch von gesteigerter Reflexaktivität berichtet [31,32] -doch sind diese Ergebnisse nicht unwidersprochen [33] und daher noch keineswegs eindeutig. In anderen Studien wurden die Kraftfähigkeiten untersucht.…”
Section: Einleitung Und Problemstellungunclassified
“…In früheren Untersuchungen konnte durch die Anwendung von Tape-Verbänden und Orthesen die Einschränkung von Supinations-Bewegungen eindeutig nachgewiesen werden; gleichzeitig trat dabei auch ein neuromuskulärer stimulierender Effekt auf [29,30]. Ähnliche Befunde wurden mit anderen Verfahren auch von anderen Autoren dargestellt [27,31]. Studien, in denen die Auswirkungen der ständigen Anwendung von Stabilisierungshilfen, beispielsweise auf die Peronealmuskulatur, untersucht wurden, finden sich in der Literatur nur selten.…”
Section: Diskussionunclassified